(untitled) (Proceedings of the International Conference on Gender and Sexuality, 2024)
Homosexuality is a controversial issue among some rural African ethnic groups such as the Vendas and the Zulus as established by research. To gain more insights into this conundrum, a qualitative study, using a constructivist research paradigm and an exploratory research design was conducted to explore Northern Sotho traditional healers’ perceptions of male homosexuality in relation to ancestral calling, spirit possession, loss and initiation in the Capricorn District of Limpopo province, South Africa. Ten participants (7 females and 3 males) between the ages of 32 and 72 with grade 12 highest education level formed part of the study. Data was collected through individual face-to-face semi-structured interviews. Data was analyzed with Thematic Analysis (TA) and 10 main themes, and 9 sub-themes emerged from the data, although only 4 of the main themes and 1 sub-theme are presented in this paper. The results indicate that the traditional healers are un-accepting of male homosexuality as they consider it to be inconsistent with their culture, although there are circumstances where exceptions can be made such as when a male homosexual has an ancestral calling or is sick. The study contributes to knowledge by providing new insights and suggestions for Indigenous Knowledge Systems (IKS), academic training, legislation, and policy development concerning male homosexuality and indigenous culture. Future studies ought to investigate how male homosexuals residing in rural African communities are treated to gain insights into their experiences.